Efforts to Improve Community Welfare Through Farming Group Empowerment from an Islamic Economic Perspective - Efrina, Lisa (Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aimed to determine the level of community welfare through farmer group empowerment from an Islamic economic perspective. This research includes field research (field research). The method used in this research is qualitative data analysis with a descriptive nature. The results showed the implementation of community empowerment for the prosperous Sido farmer group towards improving the welfare of the community in Sidoharjo Village through counseling programs and skills training. The implementation of community empowerment of the prosperous Sido farmer group in Sidoharjo Village can be said to be successful. The members admitted that there was an increase in knowledge and skills in agriculture, obtained new information about agriculture, increased income before they joined and after joining the prosperous Sido farmer group, and were very enthusiastic about the empowerment program. This means that the empowerment of the Sido prosperous farmer group community has a positive effect in improving the welfare of the Sido prosperous farmer group members in Sidoharjo Village, Jati Agung District, South Lampung Regency, and the Sido prosperous farmer group member community can already be said to be a prosperous society. Empowerment in the view of Islamic Economics is seen from the principles of Islamic Economics that community empowerment for members of the prosperous Sido farmer group is following the rules or limitations in Islam that Allah SWT has determined to achieve falah in the world the hereafter and for welfare. The community members of the prosperous Sido farmer group are following welfare in the view of Islamic Economics